Planejamento estratégico: aplicação nas micro e pequenas empresas - Boechat, Marcelo Nascimento (2008)
The Strategic Planning is the managerial process that it makes possible to establish one heading for being followed by the company, with views to obtain an optimization level in this relationship with the external atmosphere. In the small company¿s improvement the general performance of the results and the use of resources, however it is still little known and used. These organizations need administration tools to be capable to promote the business growth and to guarantee the survival more and more in this market competitive. This way, it is done necessary to approach the strategic planning in a complex less way and the objective of this research is to provide larger knowledge regarding the Strategic Planning in the personal computer and small companies, to verify the limitations in the implantation, to analyze the reasons for the low effectiveness of the use in companies of this load and to identify the consultants interviewees close to the best way to implant it. The understanding of these limitations aids the small intrepreneur and the consultant in the implantation of the strategic planning as increment of competitiveness as this use provides reflections, guidelines for the activities of the organization, as well as it makes possible adaptation and answer capacity to the changes of the market.